Ice Show - Holden, Constance (Science (American Association for the Advancement of Science), 1997)
New York's American Museum of Natural History will host a 6-month exhibit on diamonds that opens Nov 1 featuring a simulation of a mine tunnel, a hands-on model of a diamond crystal and a workshop where gem cutters demonstrate their craft. This is the most comprehensive exhibition ever done on the subject of diamonds.